2022
DOI: 10.1038/s41571-022-00668-4
|View full text |Cite
|
Sign up to set email alerts
|

Senescence and cancer — role and therapeutic opportunities

Abstract: Cellular senescence is a state of stable, terminal cell cycle arrest associated with various macromolecular changes and a hypersecretory, pro-inflammatory phenotype. Entry of cells into senescence can act as a barrier to tumorigenesis and, thus, could in principle constitute a desired outcome for any anticancer therapy. Paradoxically, studies published in the past decade have demonstrated that, in certain conditions and contexts, malignant and non-malignant cells with lastingly persistent senescence can acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
206
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(209 citation statements)
references
References 248 publications
3
206
0
Order By: Relevance
“…In turn, cells trigger firm proliferative arrest and senescence by initiating key cell cycle arrest genes such as TP53, p16INK4a, and p21, which counteract malignant growth. 485 In PTEN loss-induced cellular senescence, cells activate mTOR-p53-mediated signaling to block the cell cycle, and induce a cellular senescence phenotype. 486 In addition, cells undergoing senescence enhance tumor suppression by cell-extrinsic manner.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, cells trigger firm proliferative arrest and senescence by initiating key cell cycle arrest genes such as TP53, p16INK4a, and p21, which counteract malignant growth. 485 In PTEN loss-induced cellular senescence, cells activate mTOR-p53-mediated signaling to block the cell cycle, and induce a cellular senescence phenotype. 486 In addition, cells undergoing senescence enhance tumor suppression by cell-extrinsic manner.…”
Section: Cancermentioning
confidence: 99%
“…Senescent cells promote senescence or death of neighboring cells through direct cell-cell interactions or inflammatory SASP factors release, causing increased production of ROS and a sustained DNA damage response, thereby also limiting the proliferation of neighboring precancerous or cancerous cells. 485 In addition, SASP factors containing immune surveillance enhancers such as CCL2, IL-15, CXCL1, etc. that drive macrophages, lymphocytes and NK cells to recruit to tumor sites, which activate immune surveillance.…”
Section: Cancermentioning
confidence: 99%
“…However, on the other hand it has been reported that senescent cells may also promote tumor growth. Important to mention are the tumor-promoting properties of SASP including chronic inflammation, angiogenesis, stemness, migration and invasion [ 49 , 50 ]. Therefore, TIS is an important determinant of therapy response for the clinical outcome for patients and rather under-investigated.…”
Section: Therapy-induced Cellular Senescence In Pcamentioning
confidence: 99%
“…Upon p53 activation, the up-regulation of p21 (also known as CDKN1A) blocks the formation of cyclin-cyclin-dependent kinase (CDK) complexes. p16 Ink4A (also known as CDKN2A) directly binds to and inhibits the interaction between CDK4/6 and cyclin D. When CDKs are inhibited by p21 and p16 Ink4A , RB remains hypophosphorylated and interacts with the transcription factor, E2F, leading to irreversible cell cycle arrest [ 1 , 10 ]. Although senescent cells are characterized by growth arrest, they remain metabolically active.…”
Section: Cellular Senescence: Types and Characteristicsmentioning
confidence: 99%